Modelling pension fund investment behaviour - Blake, David, 1954- (Routledge, 1992)
This book is about: UK pension funds and their investments; A theoretical model of portfolio behaviour; The investments and returns of private sector pension funds; Modelling the expected returns and risks of private sector pension funds....